Nanoflaky MnO2/functionalized carbon nanotubes for supercapacitors: an in situ X-ray absorption spectroscopic investigation. Issue 5 (16th December 2014) - Chang, Han-Wei; Lu, Ying-Rui; Chen, Jeng-Lung; Chen, Chi-Liang; Lee, Jyh-Fu; Chen, Jin-Ming; Tsai, Yu-Chen; Chang, Chien-Min; Yeh, Ping-Hung; Chou, Wu-Ching; Liou, Ya-Hsuan; Dong, Chung-Li
Abstract : The surfaces of acid- and amine-functionalized carbon nanotubes were decorated with MnO2 nanoflakes as supercapacitors by a spontaneous redox reaction. Abstract : The surfaces of acid- and amine-functionalized carbon nanotubes (C-CNT and N-CNT) were decorated with MnO2 nanoflakes as supercapacitors by a spontaneous redox reaction. C-CNT was found to have a lower edge plane structure and fewer defect sites than N-CNT. MnO2 /C-CNT with a highly developed surface area exhibited favorable electrochemical performance. To determine the atomic/electronic structures of the MnO2 /functionalized CNTs (MnO2 /C-CNT and MnO/N-CNT) during the charge/discharge process, in situ X-ray absorption spectroscopy (XAS) measurements were made at the Mn K-edge. Both C-CNT and N-CNT are highly conductive. The effect of the scan rate on the capacitance behavior was also examined, revealing that the π* state of CNT and the size of the tunnels in pseudo-capacitor materials (which facilitate conduction and the transport of electrolyte ions) are critical for the capacitive performance, and their role depends on the scan rate. In the slow charge/discharge process, MnO2 /N-CNT has a more symmetrical rectangular cyclic voltammetry (CV) curve. In the fast charge/discharge process, MnO2 /C-CNT with a highly developed surface provides fast electronic and ionic channels that support a reversible faradaic redox reaction between MnO2 nanoflakes and the electrolyte, significantly enhancing its capacitive performance over that of MnO2 /N-CNT. The MnO2 /C-CNT architecture has great potential for supercapacitor applications. The information that was obtained herein helps to elucidate CNT surface modification and the design of the MnO2 /functionalized CNT interface with a view for the further development of supercapacitors. This work, and especially the combination of CV with in situ XAS measurements, will be of value to readers with an interest in nanomaterial, nanotechnology and their applications in energy storage.